Ten important questions/issues for ethnobotanical research - Albuquerque, Ulysses Paulino de (2019)
For at least 30 years researchers have called for a deeper reflection on the paths we desire for ethnobotanical research. Although the discipline of ethnobotany is growing, as measured by the number of publications in the area, there is still work to be done regarding the homogeneity of theoretical and methodological approaches and the implications of ethnobotanical research findings for society as a whole. In this article we present 10 questions/issues that we believe can guide the research and actions of ethnobotanists for the coming years.